Promoting environmental sustainability in the artisanal and small-scale mining sector in Tanzania - Abel Kinyondo; Christopher Huggins (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This study examines the interaction between formalization of the artisanal and smallscale mining subsector and the regulation of negative environmental impacts in Tanzania. Formalization generally seeks to move the artisanal and small-scale mining subsector to legal status. Using documents, reviews, and interviews with key informants, the study suggests that there is generally no automatic connection between formalization of artisanal and small-scale mining and improvement of environmental protection in Tanzania. The reasons behind this situation include lack of funding, limited capacity, poor coordination, the nomadic nature of artisanal and smallscale mining operations, and using formalization as a revenue-increasing tool. To address this situation, we propose the formation of a well-funded umbrella body that only deals with the artisanal and small-scale mining subsector and formulation of an artisanal and small-scale miningspecific legal framework that delineates responsibilities of different artisanal and small-scale mining regulatory agencies to avoid overlaps and gaps. Moreover, the capacity of artisanal and small-scale mining associations should be strengthened to enable them to promote environmentally sustainable practices and engage meaningfully in stakeholder consultation meetings.
Keywords: Q52; Q53; Q57; Q58; 330; formalization; artisanal and small-scale mining; coordination; environmental protection; Tanzania